Assessment of Turning Performance and Muscle Coordination in Individuals Post-Stroke - Lewallen, Lindsey K. (J Biomech, 2020)
Turning is an important activity of daily living and often compromised post-stroke. The fall rate for individuals post-stroke while turning is nearly four times as high compared to healthy adults, with most falls resulting in injury. Thus, there is a need for evidence-based rehabilitation targets to improve turning performance for individuals post-stroke. To produce well-coordinated movements, muscles can be organized into muscle modules (i.e., groups of co-excited muscles). Post-stroke these modules can be merged, leading to impaired muscle coordination and walking performance. However, the relationship between impaired coordination and turning performance is not well understood. Thus, the purpose of this study was to analyze the influence of impaired muscle coordination (i.e., merged modules) on turning performance (i.e., time and number of steps required to complete a turn, and smoothness and balance control during the turn). Individuals post-stroke and healthy controls performed three tasks including overground straight-line walking, a 90-degree turn, and a 180-degree turn. The number of muscle modules during straight-line walking were determined using non-negative matrix factorization. During 180-degree turning, those with two modules took longer to turn, used more steps and had less smooth movement. Those with reduced module complexity exhibited diminished balance control during both 90-degree and 180-degree turning. These results suggest obtaining independent modules should be an important aim in locomotor therapies aimed at improving turning performance. In addition, the time it takes to complete a 180-degree turn may give useful clinical insight into impaired muscle coordination post-stroke.